2021
DOI: 10.1111/jipb.13150
|View full text |Cite
|
Sign up to set email alerts
|

The rice Raf‐like MAPKKK OsILA1 confers broad‐spectrum resistance to bacterial blight by suppressing the OsMAPKK4–OsMAPK6 cascade

Abstract: Mitogen-activated protein kinase kinase kinase (MAPKKK) are the first components of MAPK cascades, which play pivotal roles in signaling during plant development and physiological processes. The genome of rice encodes 75 MAPKKKs, of which 43 are Raf-like MAPKKKs. The functions and action modes of most of the Raf-like MAPKKKs, whether they function as bona fide MAPKKKs and which are their downstream MAPKKs, are largely unknown. Here, we identified the osmapkkk43 mutant, which conferred broadspectrum resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…In addition, OsMKK10-2-OsMPK6 responds to SA-mediated plant pathogen defense responses through the phosphorylation of WRKY45 [ 72 ], and OsRLCK185 (receptor-like cytoplasmic kinase) converts immune signals perceived by PAMP effector rice chitin elicitor receptor kinase 1 (OsCERK1) and activates the downstream OsMAPKKKε–OsMKK4–OsMPK3/6 pathway [ 73 ]. Studies have also shown that OsMKK3–OsMPK7–OsWRKY30 and OsMKKK43-OsMKK4–OsMPK6 can promote rice bacterial blight resistance [ 74 , 75 , 76 ], while OsMPK15 plays a negative role in Magnaporthe oryza and Xoo tolerance through the SA and JA signaling pathways [ 77 ]. The OsMKK2–OsMPK1 module positively regulates ROS-dependent blast disease (susceptibility)-related cell death in M. oryzae infection [ 78 ].…”
Section: Mapk Cascades Are Involved In a Variety Of Signal Transducti...mentioning
confidence: 99%
“…In addition, OsMKK10-2-OsMPK6 responds to SA-mediated plant pathogen defense responses through the phosphorylation of WRKY45 [ 72 ], and OsRLCK185 (receptor-like cytoplasmic kinase) converts immune signals perceived by PAMP effector rice chitin elicitor receptor kinase 1 (OsCERK1) and activates the downstream OsMAPKKKε–OsMKK4–OsMPK3/6 pathway [ 73 ]. Studies have also shown that OsMKK3–OsMPK7–OsWRKY30 and OsMKKK43-OsMKK4–OsMPK6 can promote rice bacterial blight resistance [ 74 , 75 , 76 ], while OsMPK15 plays a negative role in Magnaporthe oryza and Xoo tolerance through the SA and JA signaling pathways [ 77 ]. The OsMKK2–OsMPK1 module positively regulates ROS-dependent blast disease (susceptibility)-related cell death in M. oryzae infection [ 78 ].…”
Section: Mapk Cascades Are Involved In a Variety Of Signal Transducti...mentioning
confidence: 99%
“…OsILA1 was initially identified as a regulator of the rice lamina joint through the interaction with and phosphorylation of CCCH-tandem zinc-finger transcription factors [ 84 , 85 ]. However, it was recently reported that OsILA1 negatively regulates rice resistance to bacterial pathogens via its association with the OsMPKK4-OsMPK6 cascade [ 62 ]. OsILA1 does not interact with OsMPKK4 in yeast cells but phosphorylates OsMPKK4 in vitro, mainly at the T34 site located in the N-terminal region ( Table 2 ).…”
Section: Uncanonical Regulation Of Mapk Cascades By Mapkkksmentioning
confidence: 99%
“…For instance, overexpression of a constitutively activated form of calcium-dependent protein kinases OsCDPK1 confers Xoo resistance by affecting OsPR10a expression in rice [ 48 ]. OsILA1, a Raf-like MAPKKK, functions as a negative regulator and acts upstream of the OsMAPKK4–OsMAPK6 cascade against Xoo [ 49 ]. Unlike the type of genes mentioned above, lc7 , encoding a mutant ferredoxin-dependent glutamate synthase 1 (Fd-GOGAT1), promotes ROS accumulation in the leaves and has high broad-spectrum resistance against seven Xoo strains [ 50 ].…”
Section: Identified Rice Broad-spectrum Disease Resistance Genes In Past 10 Yearsmentioning
confidence: 99%